A 3D SPH–FE coupling for FSI problems and its application to tire hydroplaning simulations on rough ground - Hermange, C.; Oger, G.; Le Chenadec, Y.; Le Touzé, D. (Computer methods in applied mechanics and engineering, 2019)
A 3D fluid–structure coupling between Smoothed Particle Hydrodynamics (SPH) and Finite Element (FE) methods is proposed in this paper, with its application to complex tire hydroplaning simulations on rough ground. The purpose of this work is to analyze the SPH–FE coupling capabilities for modeling efficiently such a complex phenomenon. On the fluid side, the SPH method is able to handle the three complex interfaces of the hydroplaning phenomenon: free-surface, ground/fluid and fluid/tire interfaces. On the solid side, the FE method is used for its ability to treat tire–ground contact. A new algorithm dedicated to such SPH–FE coupling strategies is proposed to optimize the computational efficiency through the use of differed time steps between fluid and solid solvers. This way, the number of calls to the FE solver is minimized while maintaining the accuracy and stability of the coupling. The ratio between these respective time steps relies on a control procedure based on pressure loading. The present 3D SPH–FE model is first validated with different academic test cases and experimental data before considering the complex problem of the 3D hydroplaning simulations. Hydroplaning simulations are performed and analyzed on 3D configurations involving both smooth and rough grounds. •A 3D fluid–structure coupling between Smoothed Particle Hydrodynamics (SPH) and Finite Element (FE) methods is carried out to model hydroplaning problems.•An optimized cost-reducing coupling algorithm is proposed with a control based on pressure loading to preserve the accuracy and stability of the coupling.•A methodology is proposed to model the hydroplaning problem helping in understanding the mechanisms at the origin of the phenomenon showing a significant contribution of the road type.•It is emphasized that the road roughness leads to an increase of the fluid loading which are responsible for a loss of contact between the tire and the ground.